Comparison of Bankruptcy Concepts and Procedures in Islamic Economic Law and Indonesian Bankruptcy Law - Nursyamsudin, Febriyana; Mukhlas, Oyo Sunaryo; Sururie, Ramdani Wahyu (CV. Strata Persada Academia, 2025)
This study examines and compares the concepts and procedures of bankruptcy in Islamic economic law (At-Taflis wal Hajr) and Indonesian Bankruptcy Law (Law No. 37/2004 on Bankruptcy and Suspension of Debt Payment Obligations). Utilizing a normative legal research design with a qualitative, descriptive-analytical approach, this study relies on secondary data derived from Islamic legal sources (Qur’an, Hadith, classical fiqh literature, and scholarly fatwas) and Indonesian statutory regulations. The analysis applies a comparative legal method supported by content analysis to identify similarities, differences, strengths, and limitations within both legal systems. Findings reveal that while both frameworks share the fundamental aim of resolving debt disputes, protecting creditor rights, and distributing debtor assets equitably under judicial supervision, they differ significantly in their normative underpinnings. Islamic law embeds moral and social dimensions, treating bankruptcy as a remedial mechanism aligned with communal responsibility, whereas Indonesian positive law prioritizes procedural certainty and institutional enforcement to ensure legal and economic order. The study suggests harmonization through integrating procedural clarity with ethical and social responsibility measures from Islamic jurisprudence to strengthen bankruptcy governance in Indonesia.